Capsule–Capsule Conversion by Guest Encapsulation. (6th January 2016) - Wang, Shitao; Sawada, Tomohisa; Ohara, Kazuaki; Yamaguchi, Kentaro; Fujita, Makoto
Abstract: Guest‐induced M18 L6 –M24 L8 capsule–capsule conversion is reported. Both capsules are composed of Pd II ethylenediamine units (M) and 1, 3, 5‐tris(3, 5‐pyrimidyl)pyrimidine (L), and form trigonal bipyramidal (M18 L6 ) and octahedral (M24 L8 ) closed‐shell structures with huge hydrophobic inner spaces. The M18 L6 trigonal bipyramid is converted to the M24 L8 octahedron through encapsulation of large aromatic guests, with the latter capsule possessing a cavity volume three times larger than the former. Despite the dynamic properties of the capsule host, the encapsulated guests are difficult to extract and are thus isolated from the external environment.